Soil modulation of Quaternary glacial-interglacial cycles - Gregory J. Retallack (Geoderma)
Sinusoidal Milankovitch orbital variations do not match the sawtooth pattern of descent into glaciation followed by abrupt termination to greenhouse interglacials seen in records of marine shale, speleothems, and ice cores. Also, climatic response for the past million years has fallen on the weakest Milankovitch forcing of eccentricity (100 ka). Strong obliquity forcings (42 ka) dominate early Pleistocene and Tertiary paleoclimatic records. Both the saw-tooth pattern and mid-Pleistocene switch have been blamed on thermal inertia of large ice sheets or Antarctic bottom water, but this study advances a new pedogenic hypothesis. Interglacial Oxisols and Mollisols were unidirectional engines of atmospheric carbon consumption, albedo, and transpiration, that became more effective and resilient in resisting orbital and volcanic terminations due to grass-grazer coevolution. Diminished carbon consumption in a world of widespread Gelisols and Aridisols allowed abrupt glacial termination by accumulated volcanic CO2.